Hydraulic stability of interlocking concrete unit-V (ICU-V) - Noor, N.D.M. (Trans Tech Publications Ltd, 2014)
Continuous research is conducted to improve the available coastal protection scheme, including to develop an innovative concrete armor unit with interlocking capability. Interlocking Concrete Unit-V (ICU-V) has light weight characteristic and developed specifically for mild wave condition. This paper discusses the performance of ICU-V represented by the Stability coefficient, KD and results of the damage progression investigation under different wave conditions. These were achieved by conducting a 2-D physical model investigation by using JONSWAP random wave spectrum. The damage ratio method was used to assess the damage progression. The optimum KD obtained was 12 with highest damage level of 0.4, which is comparable with available armor units. Â© (2014) Trans Tech Publications, Switzerland.